[Kalendarz podziemny na rok 1988 wydany przez Niezależną Oficynę Wydawniczą]. . Unofficial calendar for 1988 by Niezależna Oficyna Wydawnicza (Niezależna Oficyna Wydawnicza, 1988)
Calendar in form of a sticker with black and red print on white paper. Months and days in "Solidarity" font. Price: 200 zł.